The heritage as an educational policy: analysis and perspectives from Peruvian regulations (2023) - Postigo Echaiz, Wilmer Eduardo (2024)
As a cross-cutting pedagogical approach, heritage education has gained significant relevance in the educational institutions of many countries in recent decades. However, governments have unevenly applied this educational practice, as reflected in the regulatory frameworks of their policies. Peru, a multicultural nation, contains diverse cultural manifestations that intertwine, creating a context favouring heritage education’s implementation as a coherent public policy. Therefore, the main objective of this research is to analyse the characteristics and general guidelines of Peruvian educational policy as it relates to heritage education in the year 2023. Also, as a secondary objective, contextualising this policy in the South American context, with the review of the heritage education policies of Brazil, Ecuador, Colombia, Chile, and Bolivia, to obtain a broader understanding of it. The methodology employed consisted of a documentary review of official information issued, mainly by the governing bodies of education (Ministry of Education) of Peru and the countries mentioned above. In conclusion, it has been determined that there is no policy in heritage education in Peru, but rather a series of principles associated with the field of art and culture, which, in a poorly articulated manner, integrates heritage from a pedagogical perspective.